International Youth Alienation and Disengagement: Are "Care-Less" Institutions to Blame?. Issue 4 (2nd October 2019) - Fourie-Malherbe, Magda; Schreiber, Birgit
Abstract: The majority of voters in South Africa still do not take democratic elections for granted, but the decline in voting participation is a cause for concern in South Africa, as in other parts of the world. In addition, widespread student protests at higher education institutions during 2015 and 2016, including those at African and South African institutions, were alarming. The reasons for student discontent are diverse, and the authors propose in this article that the voter disengagement and student protests are symptoms of much more sinister underpinnings largely connected to neo-liberal changes in South Africa higher education. This article discusses these trends of voter disengagement and increased student unrest and proposes that the economically and individually focused neo-liberal trends in higher education are related to these. This article proposes the relevance of the ethics of care framework for universities to mitigate these changes in higher education. Specifically, for student affairs and services in universities, the adoption of ethics of care, not only as a practice but also as a framework for student development, is discussed. The authors propose that the ethics of care can be conceptualized as an antidote to the "care-less-ness" embedded in neo-liberal influences on higher education and can enable universities to re-claim their role in developing students who are caring and living a care-filled life. A care-filled life, which involves caring for others and for community while being cared-for, and giving and receiving care, is likely to generate engaged and participative citizens.